HISTORICAL DEVELOPMENT OF STRUCTURES FOR THE PROTECTION OF POPULATION: HISTORICAL DEVELOPMENT OF STRUCTURES FOR THE PROTECTION OF POPULATION - Dimanova , Donika (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In recent years, in Bulgaria often arise disasters caused by nature or by human activity. They have a significant adverse effect on the population and the national economy. Therefore reducing the risk of disaster is essential for sustainable development of the country. The likelihood that this trend will deepen is large and there is a need for the establishment of effective governance structures.